Crustal seismic structure and anisotropy of Madagascar and southeastern Africa using receiver function harmonics: interplay of inherited local heterogeneities and current regional stress - (:unkn) unknown (My University, 2021)
Summary This study investigates the seismic structure and anisotropy in the crust beneath Madagascar and southeastern Africa, using receiver functions. The understanding of seismic anisotropy is essential for imaging past and present deformation in the lithosphere–asthenosphere system. In the upper mantle, seismic anisotropy mainly results from the orientation of olivine, which deforms under tectonic (fossil anisotropy) or flow processes (in the asthenosphere). In the crust, the crystallographic alignment of amphiboles, feldspars (plagioclase) or micas or the alignment of heterogeneities such as fractures, add to a complex geometry, which results in challenges to understanding the Earth's shallow structure. The decomposition of receiver functions into backazimuth harmonics allows to characterize orientations of lithospheric structure responsible for azimuthally varying seismic signals, such as a dipping isotropic velocity contrasts or layers of azimuthal seismic anisotropy. By analysing receiver function harmonics from records of 48 permanent or temporary stations this study reveals significant azimuthally varying signals within the upper crust of Madagascar and southeastern Africa. At 30 stations crustal anisotropy dominates the harmonics while the signature of a dipping isotropic contrast is dominant at the remaining 18 stations. However, all stations’ backazimuth harmonics show complex signals involving both dipping isotropic and shallow anisotropic contrasts or more than one source of anisotropy at shallow depth. Our calculated orientations for the crust are therefore interpreted as reflecting either the average or the interplay of several sources of azimuthally varying signals depending of their strength. However, comparing information between stations allows us to draw the same conclusions regionally: in both southern Africa and Madagascar our measurements reflect the interplay between local, inherited structural heterogeneities and crustal s
Keywords: African Research